INVITATION TO PARTICIPATE IN WORKSHOP ON RESPONSE SURFACE METHODOLOGY IN BIOPROCESSING 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, January 2016 – The School of Industrial Technology, Universiti Sains Malaysia (USM) will be organising a 2day workshop on Response Surface Methodology in Bioprocessing on the 2 and 3 of February 2016 (Tuesday and Wednesday), at the Computer Lab (Lab 114, Level 1), School of Industrial Technology, USM, Penang.